An Incremental System To Predict the Effect of Different London Dispersion Donors in All‐meta‐Substituted Azobenzenes. Issue 12 (1st February 2022) - Di Berardino, Chiara; Strauss, Marcel A.; Schatz, Dominic; Wegner, Hermann A.
Abstract: Predictive models based on incremental systems exist for many chemical phenomena, thus allowing easy estimates. Despite their low magnitude in isolated systems London dispersion interactions are ubiquitous in manifold situations ranging from solvation to catalysis or in biological systems. Based on our azobenzene system, we systematically determined the London dispersion donor strength of the alkyl substituents Me, Et, i Pr up to t Bu. Based on this data, we were able to implement an incremental system for London dispersion for the azobenzene scheme. We propose an equation that allows the prediction of the effect of change of substituents on London dispersion interactions in azobenzenes, which has to be validated in similar molecular arrangements in the future. Abstract : An incremental system for London dispersion has been developed that allows an easy back‐of‐the‐envelope estimation when systematically altering the London dispersion donors. A simple equation is proposed that nicely reproduces the experimental results within error.